If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7y + 4ab = 76 Reorder the terms: 4ab + 7y = 76 Solving 4ab + 7y = 76 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-7y' to each side of the equation. 4ab + 7y + -7y = 76 + -7y Combine like terms: 7y + -7y = 0 4ab + 0 = 76 + -7y 4ab = 76 + -7y Divide each side by '4b'. a = 19b-1 + -1.75b-1y Simplifying a = 19b-1 + -1.75b-1y
| Y-3+2Y=9 | | 3x-1+5x+5=76 | | 2X=16-(X+9) | | -15=5(24+l) | | 2x+3=3x+-4 | | 4x=(2/-2y)/4 | | 6x+4=-4x-26 | | 1/2y-3=13 | | 85.00+7.50d=130.00 | | D/-2=-48 | | 7*5=59-j | | 44+n=5*9 | | -3=x/-21 | | 5y-10=3y+26 | | 85.00+7.50d=30.00 | | (-78c)-(-75c)+(-68c)-(-54c)+12c-(-67)=(-28) | | 6+35=m-8 | | -24=h/-3 | | 3x-1-5x+5=105 | | 10z-5z-2z-3=45 | | 3x-1+5x+5=105 | | 3=f/-15 | | 92t-38t+(-79t)-(-30t)=(-75) | | 66-w=16+1 | | 3x-1-5x+5=180 | | 7c-6=29 | | 120+40r=800 | | (-25d)-(-12d)+(-37)=54 | | 5y+6=6y-7 | | K/-4=-11 | | 7c-4=29 | | (-70x)+52x+36x-(-83x)-95x=(-84) |